History of cooperation in the field of environmental protection (Eurasian Journal of Ecology, 2016)
The article is devoted to the literature review of the history of establishing international cooperation in the field of protection of the environment, but also reflects the degree to enhance the relevance of this issue forthe last 150 years.
Keywords: environmental activities sewn; international cooperation; history.